Influence of inter-fractional respiratory motion changes on dose delivery accuracy in dynamic conformal arc lung stereotactic body radiotherapy: A phantom study - Bong Kyung Bae; Sung Joon Kim; Jae-Chul Kim (PLoS ONE, 2025)
Purpose To evaluate the influence of inter-fractional respiratory motion variation on dose delivery accuracy in dynamic conformal arc lung stereotactic body radiotherapy (SBRT) using glass dosimeter and QUASAR TM respiratory motion phantom. Materials and Methods Four-dimensional computed tomography (4D-CT) was acquired using a sinusoidal respiratory waveform (amplitude: 10 mm, breaths per minute [BPM]: 20). Three glass dosimeters were positioned at the superior edge, geometric center, and inferior edge of the tumor target. Internal target volume (ITV)-SBRT and gated-SBRT plans were created and delivered under nine respiratory conditions (BPM: 10–30, amplitude: 5–30 mm). Treatment was considered acceptable if the delivered dose to the glass dosimeters remained within the D 5% –D 95% of the gross tumor volume. Results BPM had minimal effect on ITV-SBRT, with the doses delivered to the target remaining within the acceptable range for all BPMs. However, amplitude significantly affected SBRT accuracy. For ITV-SBRT, increase in amplitude caused underdose at both the superior and inferior edges. In gated-SBRT, higher amplitude led to significant underdosing at superior edge of the target than that observed in ITV-SBRT, while inferior edge remained within the acceptable dose range. Underdose worsened with increasing amplitude, and 10 mm increase from the reference caused it to fall below the acceptable range (D 95% ). Conclusion Respiratory motion significantly affects dose delivery accuracy in lung SBRT, with amplitude playing a critical role. An amplitude increase of ≥ 10 mm from CT acquisition during SBRT delivery resulted in a significant target underdosing below the clinically acceptable threshold.